Peroxiredoxin-1 Overexpression Attenuates Doxorubicin-Induced Cardiotoxicity by Inhibiting Oxidative Stress and Cardiomyocyte Apoptosis. (29th July 2020) - Jiang, Lai; Gong, Yanping; Hu, Yida; You, Yangyang; Wang, Jiawu; Zhang, Zhetao; Wei, Zeyuan; Tang, Chaoliang
Abstract : Background . Previous research has shown that peroxiredoxin 1 (Prdx1) is an important modulator of physiological and pathophysiological cardiovascular events. This study is aimed at investigating the role and underlying mechanism of Prdx1 in doxorubicin- (DOX-) induced cardiotoxicity. Cardiac-specific expression of Prdx1 was induced in mice, and the mice received a single dose of DOX (15 mg/kg) to generate cardiotoxicity. First, our study demonstrated that Prdx1 expression was upregulated in the heart and in cardiomyocytes after DOX treatment. Second, we provided direct evidence that Prdx1 overexpression ameliorated DOX-induced cardiotoxicity by attenuating oxidative stress and cardiomyocyte apoptosis. Mechanistically, we found that DOX treatment increased the phosphorylation level of apoptosis signal-regulating kinase-1 (ASK1) and the downstream protein p38 in the heart and in cardiomyocytes, and these effects were decreased by Prdx1 overexpression. In contrast, inhibiting Prdx1 promoted DOX-induced cardiac injury via the ASK1/p38 pathway. These results suggest that Prdx1 may be an effective therapeutic option to prevent DOX-induced cardiotoxicity.